Amyotrophic lateral sclerosis-associated TDP-43 mutation Q331K prevents nuclear translocation of XRCC4-DNA ligase 4 complex and is linked to genome damage-mediated neuronal apoptosis. (1st April 2019) - Guerrero, Erika N; Mitra, Joy; Wang, Haibo; Rangaswamy, Suganya; Hegde, Pavana M; Basu, Priyadarshini; Rao, K S; Hegde, Muralidhar L
Abstract: Dominant mutations in the RNA/DNA-binding protein TDP-43 have been linked to amyotrophic lateral sclerosis (ALS). Here, we screened genomic DNA extracted from spinal cord specimens of sporadic ALS patients for mutations in the TARDBP gene and identified a patient specimen with previously reported Q331K mutation. The patient spinal cord tissue with Q331K mutation showed accumulation of higher levels of DNA strand breaks and the DNA double-strand break (DSB) marker γ H2AX, compared to age-matched controls, suggesting a role of the Q331K mutation in genome-damage accumulation. Using conditional SH-SY5Y lines ectopically expressing wild-type (WT) or Q331K-mutant TDP-43, we confirmed the increased cytosolic sequestration of the poly-ubiquitinated and aggregated form of mutant TDP-43, which correlated with increased genomic DNA strand breaks, activation of the DNA damage response factors phospho-ataxia-telangiectasia mutated (ATM), phospho-53BP1, γ H2AX and neuronal apoptosis. We recently reported the involvement of WT TDP-43 in non-homologous end joining (NHEJ)-mediated DSB repair, where it acts as a scaffold for the recruitment of XRCC4-DNA ligase 4 complex. Here, the mutant TDP-43, due to its reduced interaction and enhanced cytosolic mislocalization, prevented the nuclear translocation of XRCC4-DNA ligase 4. Consistently, the mutant cells showed significantly reduced DNA strand break sealing activity and were sensitized to DNA-damaging drugs. In addition, the mutant cells showed elevated levels of reactive oxygen species, suggesting both dominant negative and loss-of-function effects of the mutation. Together, our study uncovered an association of sporadic Q331K mutation with persistent genome damage accumulation due to both damage induction and repair defects.